Work Stress And Turnover Intention: The Mediating Role Of Burnout In An Agribusiness Case Study Using The JD-R Model - Pratama, Ananda; Puteri Andika Sari (Journal of Business and Management Inaba, 2025)
This study investigates the influence of work stress on turnover intention with burnout as a mediating variable among employees at CV. Cuma Jaya Abadi (CJA), an agribusiness company in West Java. Using a quantitative explanatory design, the research integrates structured interviews, limited direct observation, and questionnaires from 59 employees. Data was analyzed using PLS-SEM with SmartPLS 4.0. Results show that work stress significantly increases burnout and turnover intention. Burnout also mediates the relationship between stress and turnover. These findings underline the importance of managing psychosocial risks in agribusiness to improve employee retention and organizational performance.